China and East Asian regional integration: Inception of ACFTA and APEC at 20 - Yeoh, Emile Kok Kheng; Yoo, Im Soo; Liong, Lionel Wei Li (Institute of China Studies, 2010)
The rapid rise of China as a major economic power within a short span of 30 years is often described as one of the greatest economic success stories in modern times. For the past 30 years, China has opened and strengthened diplomatic relations and expanded her trading network. With the rise of China as a colossal trading power, it is important and timely to study the role of China in shaping the regional trade pattern between China, East Asian countries and ASEAN. Focusing on trade relations between China, Malaysia and countries in the East Asian region, this paper examines the role of China in the Asia-Pacific trade framework in the context of APEC and analyzes the possible regional implications of ACFTA/CAFTA as part of a paradigm shift in China's trade policy with particular reference to Sino-Malaysian economic relations.